Comparative cultural factors and knowledge management and desirable proposal (Applied study: public and private banks of Khorasan Razavi province) - Reza, Karimi Moghadam (2021)
The aim of this study was to identify and compare the relationship between cultural factors and knowledge management and provide the desired model (comparative study: public and private banks in Khorasan Razavi province). The statistical population of this study included all managers and employees of public and private banks, of which 350 people were selected as a sample. Based on the results, 68 components were identified for 14 components and factors related to it. Factors related to knowledge management are categorized into 9 dimensions and factors related to organizational culture are categorized into 5 dimensions. The results show that there is a positive and significant relationship between knowledge storage indicators, knowledge organization, knowledge dissemination, knowledge absorption, knowledge creation, knowledge application, knowledge evaluation, knowledge removal, and knowledge sharing and cultural factors in public and private banks of Khorasan Razavi province. The results show that cultural factors impact on knowledge management and provide the desired model in public and private banks in Khorasan Razavi province.